Practicality and Effectiveness of Guided Discovery Learning Based-PowerPoint-iSpring Multimedia Integrated Multirepresentation and Prompting Questions on Buffer Solution Topic - Junia Putri; Guspatni Guspatni (Universitas Riau, 2022)
This study aims to determine the practicality and effectiveness of learning outcomes in PowerPoint-iSpring learning media that integrates multiple representation and prompting questions based on guided discovery learning. This research is a follow-up Research and Deevelopment (R&D) using the 4-D as the instructional model. The practicality and effectivity were obtained through research instruments is practicality questionnaire and formative test. Practicality was carried out by 10 students of class XII MIPA and two chemistry teachers at SMAN 5 Tebo, while effectivity was carried out by 28 students of class XI MIPA 3 SMAN 5 Tebo. The results of analysis on practicality data showed value of 90% (for teacher practicality) and 87% (for students practicality) both showing very practical category. The result of analysis on effectivity data showed the N-Gain value of 0,78 which was categorized as high, and the hypothesis test using the paired sample t-test showed that the learning outcomes of students after being given treatment were significantly higher than before being given treatment. Therefore, PowerPoint-iSpring learning media that integrates multiple representation and prompting questions based on guided discovery learning is practical and effective for the learning outcomes of students in class XI MIPA SMAN 5 Tebo.